Strong repulsive Lifshitz-van der Waals forces on suspended graphene - Gianluca Vagli; Tian Tian; Franzisca Naef; Hiroaki Jinno; Kemal Celebi; Elton J. G. Santos; Chih-Jen Shih (Nature Communications)
Abstract Understanding surface forces of two-dimensional (2D) materials is of fundamental importance as they govern molecular dynamics in nanoscale proximity. Despite recent understanding of substrate-supported 2D monolayers, the intrinsic surface properties of 2D materials remain vague. Here we report on a repulsive Lifshitz-van der Waals force generated in proximity to the surface of suspended graphene. In combination with our theoretical model taking into account the flexibility of graphene, we directly measured repulsive forces using atomic force microscopy. An average repulsive force of up to 1.4 kN/m2 has been detected at separations of 8.8 nm between a gold-coated tip and a sheet of suspended graphene, more than two orders of magnitude greater than the long-range Casimir-Lifshitz repulsion demonstrated in fluids. Our findings imply that suspended 2D materials could exert repulsive forces on any approaching electroneutral object in close proximity, resulting in substantially lower wettability. This could offer technological opportunities such as molecular actuation and quantum levitation.